Single walled MgF2 nanotubes - Ferreira, Marcio Douvel; Santos, Jose Divino; Taft, C. A.; Longo, Elson [UNESP]; Martins, Joao B. L. (Elsevier B.V., 2009)
We have computer-aided designed {[(MgF2)(2)](n)}(m) (with n = 6, 8, 10, 12, 14, 16, 18, 20, 30, and m = 1, 2, 3) nanotubes. The structural and electronic properties were calculated using the Hartree-Fock and B3LYP methods with the Huzinaga basis set, in order to determine charge, relative energies and optimized structural parameters. The conformational stability was investigated as a function of the unit number along the circumference and the structural parameters. The calculated geometric and electronic properties were compared with available experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Nanotubes; Ab initio; MgF2, Huzinaga basis set; B3LYP; Hartree-Fock